DIAGNOSTICS OF PREGNANT WOMEN WITH GESTATIONAL DIABETES (Journal of Pharmaceutical Negative Results, 2022)
Object: Selection of an effective method of delivery for mother and child in pregnant women with gestational diabetes.Purpose of the study: Selecting the optimal method of delivery by studying the outcome of labor for the mother and fetus in women with gestational diabetes.Material and methods: The retrospective group included 67 women who passed through the regional perinatal center, city maternity complex and family clinics No. 5, No. 6 of the city of Bukhara in the periods from 2016 to 2018. The main (prospect) group consisted of 68 women whose pregnancy proceeded against the background of overt or gestational diabetes mellitus (GDM). The control group consisted of 31 women whose pregnancy proceeded physiologically.Results and discussion: As a result of the study, the course of pregnancy and childbirth according to the history of childbirth and own observations revealed that in all (60%) pregnant women with GDM, pregnancy and childbirth proceeded with any complications, like in the mother and the fetus.Сonclusion: Thus, the optimal delivery route is selected taking into account the condition of the fetus and the level of TSH and clay hemoglobin. If pregnancy proceeded against the background of corrected diabetes with the use of the optimal insulin regimen and rational diet therapy, the absence of signs of diabetic fetopathy, then in this category of pregnant women, the delivery through the birth canal is considered the best option. The issue of delivery time is decided individually, taking into account the degree of compensation for diabetes mellitus, cervical maturity, condition and size of the fetus.